2023
DOI: 10.3390/vaccines11020451
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Antibody Response to SARS-CoV-2 Vaccination

Abstract: Vaccination plays a key role in tackling the ongoing SARS-CoV-2 pandemic but data regarding the individual’s protective antibody level are still pending. Our aim is to identify factors that influence antibody response following vaccination in healthcare workers. This single-center study was conducted at Evangelische Kliniken Gelsenkirchen, Germany. Healthcare workers were invited to answer a questionnaire about their vaccinations and adverse reactions. Subsequently, the level of anti-receptor binding domain (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Previous evidence has shown age-related predictors (likely driven by immune senescence) of waning humoral response to vaccination and, in principle, humoral responses triggered by previous SARS COV-2. 40 43 We found no difference between the ages of participants classified positive or negative by composite gold standard (i.e., median age of 34 [IQR: 26–47] and 33 [IQR: 25–47], respectively; P = 0.32); this is reassuring and suggests that study participants likely have robust immune systems, with similar waning rate between groups.…”
Section: Discussionmentioning
confidence: 55%
“…Previous evidence has shown age-related predictors (likely driven by immune senescence) of waning humoral response to vaccination and, in principle, humoral responses triggered by previous SARS COV-2. 40 43 We found no difference between the ages of participants classified positive or negative by composite gold standard (i.e., median age of 34 [IQR: 26–47] and 33 [IQR: 25–47], respectively; P = 0.32); this is reassuring and suggests that study participants likely have robust immune systems, with similar waning rate between groups.…”
Section: Discussionmentioning
confidence: 55%
“…Despite using different designs, all COVID-19 vaccines share a common goal, which is to trigger robust immunity with a strong antibody response associated with the neutralization of SARS-CoV-2. Although it has been well established that individuals develop heterogeneous immune responses and antibody levels following vaccination, age has been a pivotal factor influencing the antibody response [ 54 , 55 , 56 ]. Numerous studies investigating vaccination against influenza, hepatitis A, hepatitis B, pneumococcus, tick-borne encephalitis (TBE), tetanus, and SARS-CoV-2 have consistently shown that the antibody response following vaccination decreased with increasing age [ 33 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors contribute to the dynamics of the humoral immune response. These factors, such as age, gender, comorbidities, timing of vaccination, and previous infection history, affect not only the antibody level titer but also correlate with the severity of COVID-19 [21][22][23].…”
Section: Discussionmentioning
confidence: 99%